A modified quick PETIA for detecting anti-CCP antibodies in human serum. Issue 7 (6th March 2015) - Fu, Lin; Kang, Chun-Min; Zhang, Peng; Kang, Xia; Li, Xin; Wang, Hong-Xia; Li, Hai-Xia; Qiu, Yu-Rong
Abstract : Modified quick PETIA for detecting anti-CCP: apply a streptavidin–biotin pair as a connecting arm between polystyrene nanospheres and CCP. Abstract : In this paper, a modified particle enhanced turbidimetric immunoassay (PETIA) was established to facilitate the detection of anti-cyclic citrullinated peptide (anti-CCP) antibodies in human serum. The modified method improved the detection sensitivity by applying a streptavidin–biotin pair as a connecting arm to conjugate CCP antigens on the surface of polystyrene nanospheres. With the advantages of the nanoparticles and streptavidin–biotin pair, the modified PETIA exhibited a wide linear range for anti-CCP of 13–430 U mL −1, with a low detection limit of 12 U mL −1 . Satisfactory reproducibility of the immunoassay was demonstrated. Good correlations were obtained in the analysis between the modified method and the commercial ELISA (enzyme-linked immunosorbent assay) kit. The ROC (receiver operating characteristic) curve was plotted based on the results from measuring anti-CCP antibodies in 185 clinical serum specimens. The area under the ROC curve was 0.872. With a cut-off value of 27 U mL −1, diagnostic sensitivity and specificity were 75.68% and 91.89% respectively. The detection time by this new approach was only 20 minutes. In summary, this modified method can be used to detect anti-CCP antibodies in human serum practically and rapidly.